Pelatihan Manajemen Keuangan dan Pelaporan Keuangan pada UMKM Rumah Jamur “NANDO” - Hamdi Agustin; Azwirman Azwirman; Sri Sri Indrastuti; Eny Wahyuningsih (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The problems faced by business actors at the Nando Mushroom House are: first, the lack of knowledge of business actors about managing their business finances, such as still mixing business and household finances. Second, bookkeeping is still kept simple in their business. The problem that often occurs in home businesses is that household finances are often mixed with business finances. The targets of this Community Service program are: Nando mushroom house business actors are able to do proper bookkeeping and have skills in recording financial posts correctly. The purpose of this service is to provide training in Financial Management and Financial Reporting at the UMKM